Effect of Environmental Concern and Consumption Values on Satisfaction of Green Restaurant - Leo, Gundur - (Entrepreneurship Faculty, Universitas Garut, 2023)
This study explores the relationship between consumption values (i.e., functional, social, and emotional values) and environmental concern toward satisfaction and loyalty in green restaurants. A sample of 394 data points was gathered through online questionnaires from green restaurant customers in West Java, Indonesia. Using partial least squares to analyze the data, this study revealed that environmental concern and the value of functional, social, and emotional are significant predictors of satisfaction and behavioral intention. These findings provide guidance for green restaurant business managers to improve business competitiveness and simultaneously contribute to developing a sustainable environment.